3D+time Cadastre, possibility of implementation in Poland. Issue 335 (March 2014) - Siejka, M.; Ślusarski, M.; Zygmunt, M.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents a transition method from a 2D cadastre to a 3D+time system, using the available software, based on the official spatial data registers. For over two decades in Poland the official registers of terrain related objects have been undergoing modernisation. This modernisation focuses on the safety and protection of the rights to properties, increasing the efficiency of databases and the quality of data, as well as increasing the efficiency of planning and land management. The advanced technologies, such as CAD, GIS or DBMS, make it possible to build a digital terrain model (DTM) followed by a visualisation of surface objects, such as parcel boundaries or building outlines, in 3D. Modern relational databases and CAD tools also allow reconstruction of real estate state from any moment in history, registered in the database.